ASSESSMENT OF DIFFERENT NON-HOST CROPS AS TRAP CROP FOR REDUCING OROBANCHE AEGYPTIACA PERS. SEED BANK - Acharya, Bipana Devi (Ecoprint: An International Journal of Ecology, 2014)
Experiments were performed in pot and field conditions to evaluate effects of non-host crops on Orobanche seed bank. The two sites chosen for the study were located in highly Orobanche infested areas of Nawalparasi district, an inner Terai region of central Nepal. Pot and field experiments were conducted in the soil naturally infested with Orobanche seeds. Altogether, 21 different non-host crop species were tested in the study. Orobanche seed density in soil samples collected from pot/plot before planting and after harvest of each crop species was recorded. Data of pre-plant and postharvest were compared in order to assess the effects of the test crops on Orobanche seed density. On the basis of degree of effects on the Orobanche seed bank, the investigated crop species could be classified in to three categories: (a) non-potential trap crop: garlic, chilli, coriander, carrot, buckwheat, sunflower, french bean, pea, egg plant, potato, fenugreek, wheat and faba bean; (b) moderately potential trap crop: barley, onion, chickpea and maize; and (c) highly potential trap crops: radish, lentil, linseed, fennel and cumin. DOI: http://dx.doi.org/10.3126/eco.v19i0.9851 Ecoprint An International Journal of Ecology Vol. 19, 2012 Page: 31-38 Uploaded date: 2/14/2014